Detection of postoperative recurrence in colorectal cancer: Exploring the value of liquid biopsy - Kostiuchenko, V.; Vynnychenko, I.; Moskalenko, Y.; Pohorila, V. (Regulatory Mechanisms in Biosystems, 2025)
Rec ently, the number of publications concerning the use of liquid biopsy and, in particular, circulated tumor DNA (ctDNA) as well as the role of KRAS, BRAF, PIK3CA, and TP53 mutations for the diagnosis of early relapse in patients with colorectal cancer (CRC) has increased. However, it is necessary to accumulate a larger pool of data confirming its effectiveness and reliabi l ity for further implementation in clinical practice. The aim of this study was to determine the prevalence and impact of KRAS, BRAF, PIK3CA, and TP53 mutations on the survival of patients with stages I–III (CRC) using digital polymerase chain reaction (dPCR) and to evaluate the effectiveness of liquid biopsy in detecting ctDNA and predicting disease recurrence. 138 patients, scheduled for radical surgery for stage I–III CRC, were included in the study. DNA was extracted from tumor tissue samples and 3 plasma samples (obtained within 24 hours prior to surgery, 24 ± 1 hour and 90 ± 5 days after surgery) and then analyzed using dPCR for KRAS, BRAF, PIK3CA, and TP53 mutations. The dPCR was carried out using the QuantStudio 3D Digital PCR System (Applied Biosystems by ThermoFisher Scientific, USA) with the appropriate TaqMan Liquid Biopsy dPCR Assays (ThermoFisher Scientific, USA) (KRAS_512 (p.G12D), BRAF_476 (p.V600E), PIK3CA_775 (p.H1047R), and TP53_10662 (p.R248Q)). The studied mutations were found in 34 (24.6%) out of 138 tumor tissue samples. The prevalence of mutations in the study cohort was: KRAS – 9.4%, BRAF – 8.7%, PIK3CA – 3.6%, TP53 – 4.4%. The presence of at least one of the studied mutations significantly affected recurrence-free survival ( RFS ). The sensitivity of liquid biopsy for detecting ctDNA was 79.4%, and specificity was 100.0%. The recurrence rate was 59.3% for ctDNA-positive patients and 9.9% for ctDNA-negative patients. Liquid biopsy detected disease recurrence 2.14 months earlier than CT and colonoscopy. Ultimately, our findings support the role of liquid biopsy, particularly ctDNA, in advancing personalized treatment strategies for CRC.